SIMULATING MOLECULAR OPTICAL PROPERTIES OF POLYIMIDE FOR NONVOLATILE RESISTIVE PHOTOMEMORY DEVICES: Received: 07th July 2023 Revised: 31st October 2023, 06th November 2023, 8th November 2023 Accepted: 10th July 2023 - Wen-Luh Yang; Pei-Ying Jiang; Wei-Cheng Ou; Pin-En Hsu; Yi-Huan Pan; Tang-Yi Liu; I-Ming Tseng (MATTER: International Journal of Science and Technology, 2024)
In this study, the focus was on utilizing the polyimide (PI) thin film as a resistive conversion layer for organic polyimide-based resistive random-access memory (ReRAM) applications. We utilized the 3D molecular editor WebMO to manipulate and analyze the structures of Aromatic-PI and Quinoid-PI molecules. The molecular chain length, molecular weight, and HOMO/LUMO molecular orbitals were investigated to gain insights into the fundamental properties of PI molecular structures. The analysis revealed that the Quinoid-PI molecule exhibited a shorter molecular chain compared to Aromatic-PI, attributed to the inability of the cyclic structure in Quinoid-PI to maintain a planar conjugated structure, resulting in an uneven overall structure and reduced molecular chain length (Norcorss, 1988). The research results demonstrate that the optical energy gap of Aromatic-PI remains constant regardless of the number of molecular bonds, with a value of approximately 3.2661 eV. In contrast, for Quinoid-PI, the optical energy gap undergoes a significant decrease as the number of molecular bonds ranges from 1 to 5. As the bond count increases to 20 23, the change in the optical energy gap gradually diminishes, ultimately resulting in an optical energy gap of 0.6932 eV. This observation indicates that longer molecular chains composed of Aromatic-PI act as insulators, while Quinoid-PI transforms into a low-energy gap conductor.